Faktor-Faktor yang Berhubungan dengan Kadar Hemoglobin pada Siswa SMP - Aisyah Aisyah (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
This research intent on known factors that associated with hemoglobin rate in junior high school student at bekasi whether there is associated beetwen age, gender, breakfast habbit, ferosus tablet consuption, smoking cigarettes, knowladge about anemia, maternal education, job status, parents income and infection related with hemoglobin rate. This research used Quantitative methode with cross sectional design. Research population are students in SMP B at Bekasi year of 2015, and total sample of this research choosen by the inclusion criteria are 171 respondents Analyzis date use chisquare and multiple logistic regression. This research shows that haemoglobin rate < 12gr/100 ml in female student and < 13 gr/ 100 ml in male student are 16,5%. Bivariate analysis shows that there are significant difference in ferrosus tablet comsuption (P=0,001), knowledge rate about anemia (P=0,001), maternal education (P=0,009), Parents income (P=0,034), and infection status (P=0,040). Multivariate analysis shows that the most dominan factor are ferrosus tablet consuption (OR = 0,018 dan P=0,001) and knowladge rate about anemia (7,253 dan p-value 0,001).